Camp Center: The Big Red One - Fort Riley (Symphony in the Flint Hills, 2013)
The enduring ties between Kansas and the US Army on the Great Plains began well before Kansas was admitted to the Union on January 29, 1861. The frontier outpost we know as Fort Riley was originally called Camp Center due to its central geographical location in the United States. Camp Center had been in place since 1853.
Keywords: Big Red One; Camp Center; Fort Riley; Manhattan; Junction City; Kansas Territorial Legislature; prairie; war; army; military training; division; cavalry; 1st Infantry Division; Custer Hill; REFORGER; troops; corps; soldiers; Camp Funston; Flint Hills